A positive psychotherapy group intervention to increase distress tolerance and reduce feelings of entrapment in patients with multiple sclerosis - Yaghoob Harooni Jamalooei; Maryam Esmaeili; Ahmad Abedi; Mohammad R. Najafi (Journal of Education and Health Promotion)
BACKGROUND: Multiple sclerosis is a central neurogenic demyelinating disease. This is one of the most common neurological diseases in humans and is the most debilitating at a young age. Symptoms of multiple sclerosis include vision problems, balance problems, dizziness, sensory disturbances, chronic neuropathy, and fatigue. MATERIAL AND METHODS: A quasi-experimental study with pretest, posttest, and one-month follow-up design was conducted to evaluate the effectiveness of positive psychotherapy on distress tolerance and feelings of entrapment in 30 patients with multiple sclerosis (MS). Patients were conveniently sampled in 2021 and randomly assigned to either an experimental or control group, with 15 patients in each. The experimental group underwent eight sessions of 90-min positive psychotherapy over consecutive weeks, while the control received no therapy. Both groups completed the Simons and Gaher Distress Tolerance Questionnaire (DTS) and feeling entrapment questionnaire before and after the intervention period as pre- and posttests. Repeated measures analysis of variance (ANOVA) was performed on the collected data using SPSS 22 software to compare changes between the groups over time and assess the impact of the psychotherapy. RESULTS: Repeated measures ANOVA results showed that positive psychotherapy had a significant effect in increasing distress tolerance (Sig = 0/001 and F = 545/434) and reducing feelings of entrapment (Sig = 0/001 and F = 275/05). CONCLUSION: Positive psychotherapy increases distress tolerance and reduces the feelings of entrapment in MS patients. It is therefore suggested that interventions based on positive psychological points should be done in different centers. The context should be repeated and include larger and more ethnically and socioeconomically diverse examples.